EVALUATION OF ACUTE PHASE INFLAMMATION MARKERS IN PATIENTS WITH CHRONIC HEART FAILURE WHO HAVE RECOVERED FROM COVID-19 - Rakhmatullaeva G.K; Nazarov N.N; Donabaeva M.H. (Western European Studies, 2024)
During the COVID-19 pandemic, the mortality rate from chronic heart failure has significantly increased compared to patients with chronic heart failure who were not infected. In the early stages of the disease, the use of enzyme-linked immunosorbent assays as sensitive methods, in addition to traditional clinical and laboratory methods, is a relevant task for early detection of clinical signs of the disease. (1,2,3) The assessment of endothelial function in patients with chronic heart failure who have recovered from COVID-19 worldwide is important to prevent complications that may arise after the illness. (4,5,6) A key and important aspect of this is the determination of the quantity of endothelial dysfunction biomarkers in the blood of patients with chronic heart failure who have recovered from COVID-19
Keywords: COVID-19; acute phase inflammation markers; chronic heart failure